Roles of Non-coding RNAs and Angiogenesis in Glioblastoma - Balandeh, Ebrahim; Mohammadshafie, Kimia; Mahmoudi, Yaser; Hossein Pourhanifeh, Mohammad; Rajabi, Ali; Bahabadi, Zahra Razaghi; Mohammadi, Amir Hossein; Rahimian, Neda; Hamblin, Michael R.; Mirzaei, Hamed (Frontiers in Cell and Developmental Biology, 2021)
One of the significant hallmarks of cancer is angiogenesis. It has a crucial function in tumor development and metastasis. Thus, angiogenesis has become one of the most exciting targets for drug development in cancer treatment. Here we discuss the regulatory effects on angiogenesis in glioblastoma (GBM) of non-coding RNAs (ncRNAs), including long ncRNA (lncRNA), microRNA (miRNA), and circular RNA (circRNA). These ncRNAs may function in trans or cis forms and modify gene transcription by various mechanisms, including epigenetics. ncRNAs may also serve as crucial regulators of angiogenesis-inducing molecules. These molecules include, metalloproteinases, cytokines, several growth factors (platelet‑derived growth factor, vascular endothelial growth factor, fibroblast growth factor, hypoxia-inducible factor‑1, and epidermal growth factor), phosphoinositide 3‑kinase, mitogen‑activated protein kinase, and transforming growth factor signaling pathways.